Learning Physics in the Blended Learning mode: Input for Enhanced Strategies in Learning Physics - Candido, Keneth John O.; Capilitan, Lenilyn B.; Gillesania, King Christian C.; Silva, Noemi; Reales, Joy Mae B. (Future Science / FSH-PH Publications, 2023)
Physics is a core subject in the Science, Technology, Engineering, and Mathematics strand, and high school students and Physics teachers find the subject challenging because they had to deal with multiple representations at the same time. This study aims to know the experiences of STEM students in the blended learning mode, experiences in instructional support and the difficulties and the coping mechanism implied by the students in the blended learning mode. This study employed descriptive-qualitative research and the 19 participants were chosen using purposive sampling with inclusion criteria. In gathering data, data the researchers used an in-depth interview guide that was validated by three experts. Results show that there were 16 themes that emerged. The themes for the experiences of students in blended learning are Difficult, Browsing the Internet, Asking Help, Extra effort in studying, Material Preparation, and Self-preparation. While the themes on the experiences in the instructional mode by the students are: Guided and assisted, Helpful, and difficult. The themes on Participants’ Difficulties in Learning Physics are Difficulty in Understanding concepts, Lack of Focus and Attention, Difficulty in Assessments, and Difficulty in Problem Solving; while the themes for coping mechanisms are Learning Styles, Regulating Negative Emotions, Seek Support and Assistance. Therefore, this study implies that students must be provided more instructional support in teaching Physics. The researchers recommend this study to the STEM students, teachers, school heads, and future researchers.